WHEN GENDER AND LOOKING GO HAND IN HAND - Dussias, Paola E.; Valdés Kroff, Jorge R.; Guzzardo Tamargo, Rosa E.; Gerfen, Chip (Studies in second language acquisition, 2013)
In a recent study, Lew-Williams and Fernald (2007) showed that native Spanish speakers use grammatical gender information encoded in Spanish articles to facilitate the processing of upcoming nouns. In this article, we report the results of a study investigating whether grammatical gender facilitates noun recognition during second language (L2) processing. Sixteen monolingual Spanish participants (control group) and 18 English-speaking learners of Spanish (evenly divided into high and low Spanish proficiency) saw two-picture visual scenes in which items matched or did not match in gender. Participants’ eye movements were recorded while they listened to 28 sentences in which masculine and feminine target items were preceded by an article that agreed in gender with the two pictures or agreed only with one of the pictures. An additional group of 15 Italian learners of Spanish was tested to examine whether the presence of gender in the first language (L1) modulates the degree to which gender is used during L2 processing. Data were analyzed by comparing the proportion of eye fixations on the objects in each condition. Monolingual Spanish speakers looked sooner at the referent on different-gender trials than on same-gender trials, replicating results reported in past literature. Italian-Spanish bilinguals exhibited a gender anticipatory effect, but only for the feminine condition. For the masculine condition, participants waited to hear the noun before identifying the referent. Like the Spanish monolinguals, the highly proficient English-Spanish speakers showed evidence of using gender information during online processing, whereas the less proficient learners did not. The results suggest that both proficiency in the L2 and similarities between the L1 and the L2 modulate the usefulness of morphosyntactic information during speech processing.